The Role of Negotiations in International Relations - Alsubaie, Thamer Abdullah Eid (Journal of Economic, Administrative and Legal Sciences, 2019)
What was the sporadic intercourse to facilitate contacts among various ancient political entities in different parts of the world became organized inter-state relations between nations and states, supported diplomacy as the art of settling disputes by negotiations.Negotiations have become the essential instrument at the core of contemporary international relations that are constantly changing in time and space. The negotiations brought the shift of major importance and had direct impact on international relations. The international organizations have been empowered to assist governments of its member states in progressive liberalization of trade in all areas. Negotiations have intensified the inter-state relations contacts collection of information about the ways other societies are organized and act. Negotiations have become primary tools in building international consensus on most important issues of security, war and peace. This research aimed to assess the role of negotiations in international relations. In order to achieve this aim, the researcher reviewed articles and research that dealt with examining the origin of the research variables, and also aimed to identify the relationship between these variables. In addition to that, the researcher conducted in depth interviews with 15 key officials in Saudi Arabia. The results of the study found that effective negotiations have a positive impact on the quality of international relations. Of the main recommendations of the study is that it is essential that the negotiator have the required sets of skills to ensure an effective negotiation process.
Keywords: Negotations; International; International Relaces; Godnments; International Organizations